Disaster Mitigation is Cost Effective - Kelman, Ilan (World Bank, Washington, DC, 2013)
The author provides a briefing on cost-benefit analyses (CBA) for disaster risk reduction (DRR), stating that the most cost-effective forms of DRR investment tend to be non-structural approaches, such as land use planning, warning systems, and household-level changes. These are often backed by structural measures, making full separation difficult. Barriers to enacting DRR savings occur because political capital is rarely gained from implementing DRR, except in cases where it is visible and tangible and might not even be the most effective DRR approach. In contrast, there are political advantages to hoping that a major catastrophe will not happen while a leader is in office, but then, if a catastrophe does occur, responding with full resources, irrespective of the cost. Subsidies for individual DRR measures alongside high-profile launches for the subsidy schemes could be effective, and could be designed and implemented with explicit aspects included which gain political capital through the DRR measure, though some might have ethical concerns with this strategy.